3D printable biomaterials for dental restoration: A systematic review. (2022) - Punia, Upender; Kaushik, Ashish; Garg, Ramesh Kumar; Chhabra, Deepak; Sharma, Anmol
Abstract: This article presents in a unified way the evolution and current scenario of various rapid prototyping techniques used in dentistry and different 3D printable materials used in the amalgamation of the high-level dental composite framework. The article briefly describes the most preferred 3D printing techniques used for printing novel and conventional biomaterials, mainly (i) stereolithography, (ii) digital light processing, (iii) fused deposition modeling, and (iv) selective laser sintering. The review also discusses various types of 3D printable biomaterials used in digital dentistry, including thermoplastics, ceramics, metals in detail. Various kinds of printable biomaterials, along with their advantages, fabrication process, and primary references, are presented in tabular form. Further, the applications of additive manufacturing processes in dental prosthodontics, including the fabrication of crowns, bridges, and dentures, are also discussed. This technical review has primarily two objectives: (i) dental professionals can select the most suitable additive manufacturing technique and biomaterial for their end application (ii) identification of existing potential research gaps for the researchers and doctors working in this area.